Assessment of a New Formulation of Sildenafil on Common Practice: An Observational Study. (2nd June 2022) - Droupy, Stéphane; Colson, Marie Hélène
Abstract : Erectile dysfunction (ED) has a significant impact on the quality of life of patients. Xybilun® (IBSA Pharma SAS, France) is a new formulation of sildenafil in an orodispersible film (ODF). This study aims to assess the response rate (RR), satisfaction with, and safety of sildenafil-ODF in daily practice in France. Patients aged ≥18 years with ED were included in four groups: Group 1 mild, Group 2 moderate, Group 3 severe ED, according to the International Index for Erectile Function (IIEF)-6 subscore, never treated with phosphodiesterase inhibitors (PDE)5-I; Group 4, patients previously treated with another PDE5-I. Patients were evaluated at baseline (V1), one (V2), and three (V3) months. The RR and satisfaction were assessed using the IIEF-6 subscore questionnaire, a 5-point Likert scale, and a Global Assessment Question (GAQ). The primary endpoint for Groups 1 to 3 was the RR according to Rosen criteria at V3 compared to V1. For Group 4, the primary endpoint was the RR, defined as the satisfaction compared with previous treatment. Secondary endpoints were the RR at V2 compared to V1, the evolution of IIEF-6 and IIEF-15 scores, dose adjustment, satisfaction, convenience, and safety. One hundred and five patients were enrolled, 83 analysed. The RR at V3 was 100% (Group 1); 75% (Group 2); 65.2% (Group 3); and 84.2% (Group 4). The overall RR was 78.3%. Secondary parameters confirmed the satisfaction with sildenafil-ODF, with 81.6% of patients very satisfied at V3. No Serious Adverse Events (SAEs) were observed. In conclusion, sildenafil-ODF seems beneficial for patients irrespective of the severity of the ED. This study confirms in the context of daily clinical practice the satisfaction of patients with sildenafil-ODF. Data suggest that the availability of the intermediate dose of 75 mg could add greater flexibility to the therapy.